About why the "Novela de la tía fingida" is by Quevedo - Baras Escolá, Alfredo (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
After a long century of attributing the anonymous  text La tía fingida to Cervantes, it seems clear that none of the proofs used to defend this authorship offers a solid foundation on which to sustain it. A new attribution to Francisco de Quevedo is proposed by comparing recurring voices or expressions almost exclusive of the peculiar quevedesco erotic universe, as well as characters, scenes, special pronominal uses and figures of speech, to conclude that no contemporary author but Quevedo could create the novel.Keywords: Quevedo / Cervantes / Anonymous attribution / Pronominal uses / Erotic vocabulary.
Keywords: Quevedo; Cervantes; Anonymous attribution; Pronominal uses; Erotic vocabulary